Next-generation ammonia pretreatment enhances cellulosic biofuel production - Sousa, Leonardo da Costa; Jin, Mingjie; Chundawat, Shishir P. S.; Bokade, Vijay V.; Tang, Xiaoyu; Azarpira, Ali; Lu, Fachuang; Avci, Utku; Humpula, James; Uppugundla, Nirmal; Gunawan, Christa; Pattathil, Sivakumar; et al. (Energy & Environmental Science, 2016)
A new liquid ammonia pretreatment methodology called Extractive Ammonia (EA) was developed to simultaneously convert native crystalline cellulose I-beta (CI) to a highly digestible cellulose IIII (CIII) allomorph and selectively extract up to B45% of the lignin from lignocellulosic biomass with near-quantitative retention of all polysaccharides. EA pretreated corn stover yielded a higher fermentable sugar yield compared to the older Ammonia Fiber Expansion (AFEX) process while using 60% lower enzyme loading. The EA process preserves extracted lignin functionalities, offering the potential to co-produce lignin-derived fuels and chemicals in the biorefinery. The single-stage EA fractionation process achieves high biofuel yields (18.2 kg ethanol per 100 kg untreated corn stover, dry weight basis), comparable to those achieved using ionic liquid pretreatments. The EA process achieves these ethanol yields at industrially-relevant conditions using low enzyme loading (7.5 mg protein per g glucan) and high solids loading (8% glucan, w/v).